Smiling, Yawning, Jaw Functional Limitations and Oral Behaviors With Respect to General Health Status in Patients With Temporomandibular Disorder—Myofascial Pain With Referral - Kuć, Joanna; Szarejko, Krzysztof Dariusz; Gołȩbiewska, Maria (Frontiers in Neurology, 2021)
Background: The temporomandibular joint is the one of the most important joints in the human body. It enables numerous orofacial functions such as mastication, swallowing, breathing, speech, emotional communication and facial expressions. The aim of the study was to evaluate the prevalence of jaw functional limitations and oral behaviors with respect to general health status in patients with temporomandibular joint disorders – myofascial pain with referral. Materials and methods: The study group consisted of 50 individuals (37 females and 13 males) with complete natural dentition. The average age was 23.36 years with ± 0.30 as a standard error. All subjects underwent clinical examination and were diagnosed with myofascial pain with referral according to the Diagnostic Criteria for Temporomandibular Disorders. The survey was conducted in connection with the Jaw Functional Limitation Scale -8 (JFLS-8), Jaw Functional Limitation Scale-20 (JFLS-20), Patient Health Questionnaire-4 (PHQ-4), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-15 (PHQ-15) and Oral Behaviors Checklist (OBC). Results: The most common functional problems in the entire study group were chewing tough food and yawning. In terms of gender, statistically significant differences were noted for chewing tough food and smiling (p = 0.015451; p = 0.035978, respectively). With respect to Bonferroni correction and Benjamini-Hochberg procedure, the observed differences were not statistically significant. There were no statistically considerable differences in mastication, mandibular mobility, verbal and emotional communication or global limitations (p > 0.05). Over half (56%) of the respondents had depression of varying severity. Somatic symptoms of different severity were found in 78% of the patients, and 44% of the respondents declared anxiety disorders. The score of the Oral Behavior Checklist (OBC=27.18) highlighted a high tendency for developing craniomandibular disorders. Conclusion: Patients with myofascial pain with referral, demonstrated a disturbed biopsychosocial profile. The restrictions in yawning and smiling as well as limitations in mastication, mobility, verbal and emotional communication and global limitations appear to be significant predictors of craniomandibular dysfunction. Depression, stress, and somatic disorders are important factors predisposing patients to the occurrence of myofascial pain with referral. The progression of oral behaviors may indicate the role of somatosensory amplification.